Chapter 29: Legume Production in Florida: Snapbean, Lima Bean, Southernpea, Snowpea - Stephen M. Olson; Eric H. Simonne; William M. Stall; Susan E. Webb; Timothy G. Taylor; Scott A. Smith; Aaron J. Palmateer (EDIS)
This document is HS727, Horticultural Sciences Department, UF/IFAS Extension. Published November 2006.